Pengaruh media pembelajaran kartu bicara terhadap keterampilan berbicara dan materi debat - Ela Resti Nur'aeni; Hany Uswatun Nisa; Ghufroni Ghufroni (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims.to determine.the influence.of speech.card learning media on speaking skills and the influence of speech card learning media in debate materials in class X science SMA N 1 Prohibition, using the type of experimental quantitative research, the population of class X IPA SMA N 1 Prohibition and samples of class X IPA 1 as an experimental class and X Science 2 as a control class. This research is backgrounded by the low ability to speak in front of the classroom, especially in learning Indonesian in debate materials. Data collection in this study used questionnaires, tests, and documentation. The results in this study were in the experimental class t-test and the control class in the speaking skills test questionnaire with a t value of 3,482> t table 1,690 and a sig value. (2-tailed) 0.001< 0.05. Based on the provisions applicable to the hypothesis testing that the researcher had outlined, then Ho was.rejected and Ha.was accepted. Sourced in the table, t-test data were obtained in the research class and the supervision class with a t number of 8. 920 t table 1, 690 as well as sig numbers. ( 2- tailed) 0.000< 0.05. Sourced on. that determination is to test the hypothesis that the researcher has explained, to Ho. rejected as well. Ha acquired. Until, the conclusion of this study is that there is an increase in dialogue skills that are important to accompany students in the research class and supervision classes the results of this talk card learning media are estimated to have consequences in learning Indonesian especially in the debate module.